2018
DOI: 10.1149/08701.0107ecst
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ X-Ray Study of Carbon Coated LiFePO4 for Li-Ion Battery in Different State of Charge

Abstract: This paper is focused on the structural characterization of commercially exploited carbon coated LiFePO4 cathode material in different state of charge. The material was measured inside of modified ECC-Opto-Std cell and X-ray characterization was performed using Rigaku Miniflex 600 HR diffractometer. The study compare two approaches used for characterization of electrodes in different state of charge: a) Fast galvanostatic mode with potential limitation typically used in the ex-situ characterizations and b) Ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…[17] Finally, fit-for-purpose cells can be designed for reflection geometry, transmission geometry or even allow both. [25,26,[35][36][37][38][39][27][28][29][30][31][32][33][34] As will be discussed later, for such cells a Be window is required for reflection geometry, while other materials (aluminized polymer, glassy carbon etc.) can be used for transmission.…”
Section: Influence Of the Cell Casing Designmentioning
confidence: 99%
“…[17] Finally, fit-for-purpose cells can be designed for reflection geometry, transmission geometry or even allow both. [25,26,[35][36][37][38][39][27][28][29][30][31][32][33][34] As will be discussed later, for such cells a Be window is required for reflection geometry, while other materials (aluminized polymer, glassy carbon etc.) can be used for transmission.…”
Section: Influence Of the Cell Casing Designmentioning
confidence: 99%
“…[31][32][33] Lithium-ion (Li-ion) batteries are the most widespread energy storage systems used in portable electronic devices, electric vehicles (EVs), stationary energy storage and satellites. [34][35][36][37][38] Nevertheless, as energy storage requirements expand, the energy density and specic capacity of commercial Li-ion batteries currently in use are proving to be insufficient for future applications. One of the possible candidates to replace Li-ion batteries are lithium-sulphur (Li-S) batteries thanks to their high theoretical specic capacity of 1675 mA h g À1 , high energy density (2600 W h kg À1 ), natural abundance, and the low cost of sulphur.…”
Section: Introductionmentioning
confidence: 99%
“…Another method for investigating lithium deposition during cycling is insitu observation using special cell holders. Insitu observations in the ECC-Opto Stud, manufactured by EL-Cells GmbH (Hamburg, Germany), on battery cells were made in [26][27][28][29][30][31][32][33] using Raman spectroscopy, X-ray diffraction (XRD) and optical analytics. Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging.…”
Section: Future Workmentioning
confidence: 99%
“…Insitu observations in the ECC-Opto Stud, manufactured by EL-Cells GmbH (Hamburg, Germany), on battery cells were made in [26][27][28][29][30][31][32][33] using Raman spectroscopy, X-ray diffraction (XRD) and optical analytics. Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging. Merryweather et al [29] used the above-mentioned cell housing for optical interferometric scattering measurements to detect single-particle ion dynamics, and Rittweger et al [30] observed the reflectivity of cathodes during charge and discharge.…”
Section: Future Workmentioning
confidence: 99%